Mucormycosis Presenting as Acute Abdomen in an Immunocompetent Child - Gupta, Vipul Kumar; Jindal, Geetanjali; Dalal, Usha R.; Punia, R. P. S.; Guglani, Vishal (Journal of Pediatric Infectious Diseases, 2015)
Mucormycosis is a rare, opportunistic fungal infection seen usually in immunocompromised individuals caused by fungi belonging to the class Zygomycetes, order Mucorales. Gastrointestinal mucormycosis is a rare infection and most commonly involves stomach, followed by the colon. Mucormycosis, especially the gastrointestinal form, has rarely been reported in immunocompetent hosts, and most such cases have been in adults. We report an interesting case of gastrointestinal mucormycosis in an immunocompetent young boy, presenting as acute abdomen, primarily involving small intestine and appendix.
Keywords: mucormycosis; appendix; immunocompetent